Prawo do informacji 2.0 – propozycje nowego podejścia do informacji publicznej - Świtała, Krzysztof (Kwartalnik Prawa Publicznego, 2012)
Right to Access public information is an essential attribute of democratic society. Law and technical solutions should make possible open, modern, transparent, safe and effective access to the high quality public information. This aim can be realized by using of Access by Design (AbD) concept, Internet web, information and communications technologies (ICT), especially Web 2.0 techniques, Data Warehouses, Business Intelligence systems, Service Oriented Architecture with XML Web Services.